Process optimization of cabinet drying of carabao mango (MangiferaindicaL.) slices using response surface methodology - Ambanloc, Paoline Angelique O. (College of Home Economics, University of the Philippines Diliman, 2018)
This study aimed to optimized the process parameters of cabinet dried mango (Mangifera indica L.) slices using response surface methodology. Specifically, the study (1) evaluated the effects of stage of ripeness of mango (Mangifera indica L. cv. Carabao) on the quality of cabinet dried mango (Mangifera indica L. cv. Carabao) slices; and (2) established and verified the optimized cabinet drying process parameters that include drying temperature (°C) and loading capacity (g/cm2) on the quality of cabinet dried mango (Mangifera indica L. cv. Carabao) slices. The appropriate stage of ripeness used throughout the succeeding phases of the study was Carabao mango at 5 days after harvest (120 days after flower induction + 5 days after harvest) with the highest overall acceptability score of 7.19 ("like moderately"). Results showed that process parameters drying temperature (°C) and loading capacity (g/cm2) had a significant (p<0.05) effect on water activity (aw), moisture content (% dry basis), color acceptability, and texture acceptability. Moreover, the optimum process parameters for cabinet dried Carabao mango slices, having a desirability score of 0.820, was established at 54.3°C with loading capacity of 0.36g/cm2. Verification experiments showed that accuracy of the generated predictive models and the validity of the optimized process parameters at significant level of α=0.05.